Identification of the fatty acids in the leaves of Premna odorata Blanco (Lamaceae) - Uy, Mylene M.; Ohta, Shinji (2015)
Two medicinal flavone aglycones, the widespread ACACETIN and the non-widespread DIOSMETIN were earlier reported as having been isolated from the dichloromethane fraction of the leaves of the Premna odorata Blanco (Lamiaceae), a native tree of the Philippines and locally known as "alagaw". This current study reports on the investigation on the hexane fraction. By MS and NMR analyses, several saturated fatty acids were determined to be present in the hexane fraction of the leaves of P. odorata.
Keywords: Plant morphology